PREDIKTOR BUDAYA ORGANISASI DI KANTOR BADAN KESATUAN BANGSA DAN POLITIK KOTA KUPANG - Jefirstson R Riwu Kore; Firda R Riwu Kore; Fellyanus Habaora (Fakultas Pertanian, 2023)
The purpose of this research is to understand and know the organizational culture in the Badan Kesatuang Bangsa and Politik of Kupang City. The research was carried out for 4 months, namely January-April 2023. The population and research sample used a census technique (saturated sample), meaning that all employees became the research sample of 31 people. Research is classified as a type of explanatory research using primary and secondary data. Techniques to obtain data by interviewing questionnaires, observation, and documentation. The operational limitations of the research are indicators of innovation and risk-taking, attention to detail, outcome orientation, people orientation, team orientation, aggressiveness, and stability. Variable measurement using a Likert scale measurement. Analysis of research data using multiple linear regression analysis techniques. The results showed that all indicators consisting of innovation and risk-taking, attention to detail, outcome orientation, people orientation, team orientation, aggressiveness, and stability had a positive and significant relationship to organizational culture, both partially and simultaneously with a determinant effect of 98 .4%.